Neural Control of Stopping and Stabilizing the Arm - Jayasinghe, Shanie A. L.; Scheidt, Robert A.; Sainburg, Robert L. (Frontiers in Integrative Neuroscience, 2022)
Stopping is a crucial yet under-studied action for planning and producing meaningful and efficient movements. In this review, we discuss classical human psychophysics studies as well as those using engineered systems that aim to develop models of motor control of the upper limb. We present evidence for a hybrid model of motor control, which has an evolutionary advantage due to division of labor between cerebral hemispheres. Stopping is a fundamental aspect of movement that deserves more attention in research than it currently receives. Such research may provide a basis for understanding arm stabilization deficits that can occur following central nervous system (CNS) damage.